Formation of volatile compounds, peptidolysis and carbohydrate fermentation by mesophilic lactobacilli and streptoccocci cultures in a cheese extract - Peralta, Guillermo Hugo (2016)
Many studies about the influence of Lactococcus lactis on cheese flavour have been reported, while the impact of mesophilic lactobacilli and Streptococcus thermophilus, either as single or mixed cultures, have been less studied. The ability of Lactobacillus paracasei 90, Lb. casei 72 (INLAIN collection) and S. thermophilus 2 (commercial strain) to produce flavour-related biochemical changes, as single or mixed (lactobacilli + streptococci) cultures, was assessed in a cheese model. These three strains, with different activities of glutamate dehydrogenase (GDH) and aminotransferases (AT), were incubated (14d/37 °C) alone or in mixed cultures in a cheese model consisting of a sterile extract of a fresh cheese. Mesophilic lactobacilli showed fermentation of carbohydrates, an increase of peptidolysis and production of volatile compounds that were correlated with their AT activities. In addition, these strains also produced completely different profiles of the amino acceptor compounds: pyruvate and α-ketoglutarate. S. thermophilus 2 increased the level of α-ketoglutarate due to its high GDH activity, but its contribution to flavour compound production was negligible; small additional changes existed when S. thermophilus 2 was mixed with the lactobacilli. Biochemical changes leading to flavour formation were mainly due to the activity of lactobacilli. Our results suggest that the AT profile and the peptidolytic activity of each strain influenced the volatilome of the extracts during incubation. So, both lactobacilli strains could be used as adjunct cultures in cheeses to increase/diversify the flavour, but more studies are needed to deepen the knowledge about the potential of S. thermophilus 2 for the production of flavour compounds.